COMPARISON OF GROWTH AND CONVERSION EFFICIENCY O:F THE FRESIDVATER PRAWN MACRO BRACHIUM MALCOLMSONII (H. MILNE EDWARDS) JUVENILES FED WITH FORMULATED AND COMMERCIAL FEEDS - SAMUEL, M. JOHN; SOUNDARAPANDIAN, P.; KONNUPANDI, T. (Journal of Indian Fisheries Association, 2015)
A nutritional study was carried out to know the feasibility of formulatedand commercial feeds on the growth of juveniles of the freshwater prawnMacrobrachium malcolmsonii. Best relative growth rate was observed forfeed 1 followed by feeds 2 and 3. Animals fed with feed I showed higherproduction than the other feeds. Higher assimilation efficiency was noticedin the animals provided with feeds 5 and 4. Higher gross arid net growthefficiencies were observed in the animals offered feed 1. Among the commercialfeeds feed 3 may considered to be suitable alternative to feed 1.Keywords : Conversion efficiency, commercial & formulated feeds